Translating Conceptual Metaphor: The Processes of Managing Interlingual Asymmetry - Massey, Gary; Ehrensberger-Dow, Maureen (Research in Language, 2017)
Encountered at all levels of language, conceptual asymmetries between source and target languages present translators with fundamental challenges that require problem awareness, problem identification and problem solving. A case in point is conceptual metaphor in translation. Versions of conceptual metaphor theory have been applied in various productoriented studies of how translators deal with the challenge of metaphor in translation. However, there is potential in combining product-oriented approaches with techniques used to access translators’ cognitive processes, although process-oriented studies on how conceptual metaphor is re-conceptualised or re-mapped in translation are still rare. Building on an exploratory study carried out at our institute, in which findings from translation process data suggest that experience and/or training appears to be a main factor in handling conceptual metaphor, we present some salient features of re-mapping metaphor. Triangulating data from target-text products, keystroke logs and retrospective verbal commentaries collected under very similar conditions in a laboratory setting, we analyse how translators at different levels of experience handle two complex conceptual metaphors. The results appear to suggest that complex metaphor might indeed be culturespecific. They also potentially indicate that re-mapping practices are a function of experience and that re-mapping to a source-language target domain could create more uncertainty than generic-level re-mapping. Both findings hold pedagogical implications, which are discussed together with some methodological issues.